2014
DOI: 10.1681/asn.2013101052
|View full text |Cite
|
Sign up to set email alerts
|

Cytomegalovirus-Responsive γδ T Cells

Abstract: Human cytomegalovirus infection in transplant recipients has been associated with adverse renal allograft outcome and with a large gd T-cell response, but whether both mechanisms are connected is unknown. We previously showed that most expanded circulating cytomegalovirus-responsive gd T cells express the Fcgreceptor CD16, suggesting that gd T cells may participate in allograft lesions mediated by donor-specific antibodies through antibody-dependent cellular cytotoxicity. Here, we show that cytomegalovirus-spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 67 publications
0
33
0
1
Order By: Relevance
“…cd T cells have also been linked to allograft rejection by observations suggesting that cd T cells expressing the Fc-c receptor CD16 bind donor-specific antibodies and participate in allograft injury via ADCC (197). CMV-infected and immunized patients have increased numbers of cd T cells and higher levels of donor-specific antibodies (198). In vivo, graft-infiltrating cd T cells in close contact with ECs were more often observed in CMV-infected patients suffering antibody-mediated rejection than with T cell-mediated acute rejection (198).…”
Section: Innate Immune Pathways In CMV Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…cd T cells have also been linked to allograft rejection by observations suggesting that cd T cells expressing the Fc-c receptor CD16 bind donor-specific antibodies and participate in allograft injury via ADCC (197). CMV-infected and immunized patients have increased numbers of cd T cells and higher levels of donor-specific antibodies (198). In vivo, graft-infiltrating cd T cells in close contact with ECs were more often observed in CMV-infected patients suffering antibody-mediated rejection than with T cell-mediated acute rejection (198).…”
Section: Innate Immune Pathways In CMV Infectionmentioning
confidence: 99%
“…CMV-infected and immunized patients have increased numbers of cd T cells and higher levels of donor-specific antibodies (198). In vivo, graft-infiltrating cd T cells in close contact with ECs were more often observed in CMV-infected patients suffering antibody-mediated rejection than with T cell-mediated acute rejection (198). The mechanisms underlying this effect are unclear but may involve the expression of "stress antigens" of CMV-infected cells recognized directly through the TCR (199).…”
Section: Innate Immune Pathways In CMV Infectionmentioning
confidence: 99%
“…We showed that CMV infection deeply reshapes the CD16þ lymphocyte compartment composition in CMVþ recipients who exhibit an equal amount of CD16þ natural killer (NK) cells and CD16þ Vd2 neg gd T cells (4). We also demonstrated that CMV-induced CD16þ Vd2 neg gd T cells could perform ADCC as well as NK cells by interacting with donor-specific antibodies and contribute to antibody-mediated microcirculation injuries during rejection (5). This implication of CMV-induced Vd2 neg gd T cells in antibody-mediated rejection seemingly contrasts with the regulatory function attributed to Vd1 gd T cells in this article (Figure 1).…”
Section: To the Editormentioning
confidence: 93%
“…Moreover, Dechanet-Merville reported that Vδ2 neg γδ T subsets may have a role during antibody-mediated rejection in patients harboring donorspecific antibodies. 8 In addition, γδ T subsets are able to recognize specific β2m-free empty HLA class I molecules 9 that are expressed at the cell surface on cellular responses to various stresses, including CMV infections or tumorigenesis. Another recently characterized unconventional T-cell subset with regulatory properties was presented by Guillaume Sarrabayrouse (Barcelona, Spain).…”
Section: Deciphering Anti-infectious Immune Responses and Pathogen-inmentioning
confidence: 99%